BEATnIk: an algorithm for the automatic generation of educational description of movies - Woloszyn, Vinicius; Machado, Guilherme M.; Palazzo, José; Saggion, Horacio; Wives, Leandro Krug (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na Educação, 2017)
Teachers have increasingly employed different methods to enrich the learning of a subject in class, drive other assignments, and meet curriculum standards. One of such methods is the use of movies as an alternative educational experience to support class discussions. In this sense, websites such as TeachWithMovies 1, arise as a valuable support to the creation of lesson plans. In this website, each movie is described as a lesson plan targeting the learning of a subject. However, the creation of such lesson plan or even a simple educational description of the movie can demand much work and time, since the text describing the teaching plan must consider educational aspects of the movie. In this work, we propose BEATnIk (Biased Educational Automatic Text summarIzation), which is an unsupervised algorithm to automatically generate movies’ summaries. Such algorithm favors educational aspects from the text to generate a biased educational summary. The experiments conducted show that our approach statistically outperforms a baseline in precision, recall, and f-score.